Balancing the books: Creating a model of responsible fashion business education. Issue 1 (1st April 2018) - Radclyffe-Thomas, Natascha; Varley, Rosemary; Roncha, Ana
This research article provides an account of a series of curriculum interventions at undergraduate and postgraduate level which engage fashion business students with real world practical and ethical complexities faced by twenty-first-century fashion businesses. Fashion education has predominantly nurtured creativity in design and promotion whilst focusing on identifying efficiencies for business operations, but increasingly the negative environmental and social impact of the global fashion industry requires a new focus on how fashion business can promote ethical and sustainable practices. The authors explore how research into sustainable fashion can be integrated into the business curriculum to guide students as they develop their personal positions on engagement with the serious issues the fashion industry faces today and tomorrow. The authors applied their research into sustainable fashion with contemporary sustainability pedagogies to design teaching delivered through case studies, lectures, seminars and assessment tasks designed to engage students with a 360-degree understanding of sustainability and to promote students' development of creative solutions to our industry's challenges. The authors sought to develop a range of teaching resources and learning sessions in line with the United Nation's Principles for Responsible Management Education (PRME) and in doing so used the lens of sustainability to explore every aspect of the fashion industry: production, design and promotion. Through the examples explored in this article, our exploratory research aims to understand how to design and implement a model of responsible fashion business education that responds to social and environmental needs and resonates with new generations of students who demonstrate an increased interest in concepts of shared social, environmental and economic value.